Implementation of Six Sigma as A Quality Control Evaluation of Routine Blood Testing on The Sysmex Xn-1000 Hematology Analyzer - Aziz Ansori Wahid; Ally Kafesa; Ni’matul Murtafi’ah; Cep Wahyu (Jurnal Penelitian Pendidikan IPA, 2026)
This study aimed to evaluate the analytical performance of routine hematology parameters on the Sysmex XN-1000 Hematology Analyzer using the Six Sigma approach. A quantitative descriptive study with an evaluative design was conducted using secondary internal quality control data collected from the Bandung City Regional Health Laboratory during February–March 2025. The analyzed parameters included hemoglobin (HGB), hematocrit (HCT), leukocytes (WBC), platelets (PLT), and erythrocytes (RBC) at three levels of control materials. Precision was assessed using the coefficient of variation (CV), while accuracy and total allowable error (TEa) were used to calculate sigma metrics. Parameters with sigma values below four were further evaluated using the Quality Goal Index (QGI). The results demonstrated that all parameters had acceptable precision, with CV values below 0.33 TEa, and total error values remained within the allowable limits. Hemoglobin and erythrocyte parameters exhibited excellent analytical performance (5–6 sigma), while leukocyte parameters achieved world-class performance (>6 sigma). Hematocrit and platelet parameters showed good performance (4–5 sigma), whereas several parameters with sigma values below four indicated problems related to imprecision, inaccuracy, or both. The findings indicate that the analytical performance of the Sysmex XN-1000 is generally satisfactory and support the implementation of Sigma Matrix-based quality control strategies to improve laboratory efficiency and reliability.